America border culture dreamer : the young immigrant experience from A to Z - Ewald, Wendy; Ewald, Wendy (Little, Brown and Company, 2018)
An alphabet book created by eighteen immigrant teens that offers a color photograph and an entry for each letter of the alphabet that relate to the first- and second-generation immigrant experience. Includes the personal stories of the teen immigrants themselves who have come to America from all around the world.